CFD modeling and validation for two-phase medium viscosity oil-air flow in horizontal pipes. Issue 5 (4th May 2019) - Pinilla, Jorge Andres; Guerrero, Esteban; Pineda, Hugo; Posada, Raquel; Pereyra, Eduardo; Ratkovich, Nicolas
Abstract: This study presents the results of a Computational Fluid Dynamics (CFD) simulation of two-phase medium viscosity oil-air flow in a 50.8 mm internal diameter horizontal pipe. Void fraction and pressure gradient predictions were validated using experimental data for four different oil viscosities (0.039, 0.06, 0.108 and 0.166 Pa s) and different flow rates varying from 0.1 to 2.9 m/s for the gas phase and from 0.01 to 2.95 m/s for the liquid phase, where four flow patterns were predicted (stratified, dispersed bubble, bubble elongated and slug flow). The obtained results of void fraction and pressure gradient presented a mean relative error of 30.04 and 21.38%, respectively. Furthermore, the CFD results were compared against 66 empirical correlations and predictions from OLGA. It was found that between the three studied methods (CFD, OLGA and empirical correlations) the CFD model outperformed the other two methods regarding the predicted flow patterns, pressure gradients and void fractions on most cases.